Tingkat Kematangan Tata Kelola Data Lembaga Pemerintah Yang Bertugas Di Bidang Pangan - Abhimata Ar Rasyiid; Betty Purwandari; Andi Kurnianto (The Indonesian Journal of Computer Science, 2024)
In order to support the national food security program, Sistem Informasi Pangan dan Gizi (SIPG) was built. This system was built by one of the government institutions tasked with food. In supporting its function, this system integrates data from internal and external institutions. Currently, not all data can be integrated into the system. The absence of policies related to reference codes and mechanisms for how data is obtained, processed, and displayed is one of the causes. To overcome this, the implementation of data governance is needed. Before doing this, it is necessary to assess the current level of data governance maturity. The assessment will provide an overview of whether the current data governance has been carried out correctly. The assessment was carried out using the Stanford Data Governance Maturity Model. Assessment results show that the current level of maturity is at level 2. While the expectation to be achieved is at level 4. To achieve the expected level of maturity, 48 recommendations are given.